CNSC-29. INVESTIGATING THE INFLUENCE OF DOPAMINERGIC ACTIVITY ON THE GLIOBLASTOMA NICHE. (14th November 2022) - Ware, Matthaeus; Pontual, Luiza Lopes; Yu, Chunying; Kushida, Michelle; Rastegar, Naghmeh; Dolma, Sonam; Dirks, Peter
Abstract: Glioblastoma (GBM) is an incurable disease of adults and children and the deadliest form of central nervous system (CNS) malignancy. Despite major advances in our understanding of GBM biology in recent years, the prognosis for patients who develop this disease has not improved. If we hope to find new treatments for GBM that are safe and effective, we desperately need to reform our thinking. The brain's chemical milieu is rich with neurotransmitters, and our lab's screen of 680 neuroactive compounds on patient-derived glioblastoma stem cells (GSCs) in vitro strongly implicates neurotransmitter pathways as critical regulators of the GSC niche. More specifically, disrupting dopamine signaling by inhibiting its receptor D4 on GSCs causes substantial GSC apoptosis in vitro and attenuates GBM growth in vivo (Dolma et al ., Cancer Cell, 2016). Dopamine (DA) is a catecholamine neurotransmitter that is essential for reward learning and movement and has numerous roles in cognition. Consequentially, dysregulation of DA signaling is associated with a diversity of brain diseases ranging from drug addiction to schizophrenia to Parkinson's. Our research aims to determine how DA signaling affects normal neural stem cell (NSC) and tumorigenic GSC populations, as we hypothesize that GSCs arising/residing in DA projection zones exploit dopaminergic (DAergic) activity for GBM growth. Toward these aims, we have developed in vivo model systems and harnessed them to study NSC and GSC niches in the context of either controlled activation or depletion of DAergic neurons. These manipulations of the brain's DAergic neurons are achieved using optogenetic stimulation, genetic depletion, and neurotoxin-mediated ablation in mice. Ultimately, unraveling the dopaminergic influence on GBM may contribute to a redeployment of existing treatments—that modulate DA signaling and are already approved to treat CNS disorders—to patients with this deadly brain cancer.